Derrida Vis-a-vis Lacan: Interweaving Deconstruction and Psychoanalysis - Hurst, Andrea (New York Fordham University Press, 2008)
Derrida and Lacan have long been viewed as proponents of two opposing schools of thought. This book argues, however, that the logical structure underpinning Lacanian psychoanalytic theory is a complex, paradoxical relationality that corresponds to Derrida's plural logic of the aporia.Andrea Hurst begins by linking this logic to a strand of thinking (in which Freud plays a part) that unsettles philosophy's transcendental tradition. She then shows that Derrida is just as serious and careful a reader of Freud's texts as Lacan. Interweaving the two thinkers, she argues that the Lacanian Real is another name for Derrida's diffrance and shows how Derrida's writings on Heidegger and Nietzsche embody an attitude toward sexual difference and feminine sexuality that matches Lacanian insights. Derrida's plural logic of the aporia, she argues, can serve as a heuristic for addressing prominent themes in Lacanian psychoanalysis: subjectivity, ethics, and language. Finally, she takes up Derrida's prejudicial reading of Lacan's Seminar on 'The Purloined Letter, 'which was instrumental in the antagonism between Derrideans and Lacanians. Although acknowledging the injustice of Derrida's reading, the author brings out the deep theoretical accord between thinkers that both recognize the power of psychoanalysis to address contemporary political and ethical issues.
Keywords: 20th Century (1901-2000); Philosophy; Deconstruction; Psychology; France